Spatiotemporal variations of surface water quality in a medium-sized river catchment (Northwestern Germany) with agricultural and urban land use over a five-year period with extremely dry summers - Buss, Johanna; Achten, Christine (The Science of the total environment, 2022)
Medium-sized rivers, which are used for intensive agriculture and urban infrastructure, are subject to manifold hydrochemical stressors. Identifying and monitoring these stressors is important for river basin management and a functioning ecosystem. To understand the spatiotemporal variation of surface water quality in a highly modified lowland river, the Münstersche Aa River (Northwestern Germany) with 62% of land used for agriculture and 26% urban/residential area, was exemplarily studied. A total of 519 samples were collected using two automated high-frequency samplers and five catchment-wide sampling campaigns. They covered the five-year period 2015–2020 and included two extremely dry summers. The Münstersche Aa catchment is dominated by low permeable strata resulting in surface water runoff (Baseflow Index: 0.41) which leads to a high amplitude of discharge variation (mean discharge: 0.7 m3/s) with high flow conditions in winter/spring, and low discharge during summer/fall. In wintertime, maximum nitrate concentrations (up to 73 mg NO3/L) and loads (up to 1300 t NO3/a; up to 98% in winter) correlate with high-flow conditions. δ18O and δ15N isotopic analysis indicated manure from farmland as the major source of nitrate whereas the impact of municipal wastewater treatment plants was neglectable. Increased nitrate concentrations are linked to the higher proportion of farmland in the upper catchment (77%) compared with the lower catchment (47%). In summertime, at extremely low flow conditions, surface water consisted of up to 100% of treated wastewater, resulting in the highest measured chloride, sodium and potassium concentrations. The river is impacted by strongly seasonal and different stressors, which can be expected to intensify with ongoing climate change. Results from this study may help to adapt monitoring schemes for the Münstersche Aa but also for other lowland streams with comparable land-use targeting the goals of the Water Framework Directive. [Display omitted] •A total of 519 samples were collected and analyzed for major ions during 2015–2020.•Up to 100% treated wastewater in German lowland river during extremely dry summers.•Merging long-term monitoring and grab sampling allows to identify major ion sources.•A load of up to 900 t of NO3/a mostly resulted from manure application.•δ15N and δ18O signature of manure in river can be distinguished from human sewage.